NAVIGATING THE PARADOX: Integrating Tradition and Educational Innovation in Indonesian Pesantren - Nisak, Zeni Hafidhotun; Pitoyo, Agus Joko; Ikhwan, Hakimul; Maryudi, Ahmad (JOURNAL OF INDONESIAN ISLAM, 2025)
This article explores the dynamic interplay between tradition and innovation in Indonesian pesantren (Islamic boarding schools), emphasizing their adaptability in the face of modern educational demands. Qualitative case studies of three well-established Islamic boarding schools of Bahrul Ulum Tambakberas Jombang in East Java, Darunnajah Jakarta, and Mathali’ul Falah Pati in Central Java is conducted. Data collection involved semi-structured interviews with key stakeholders, including kiai, teachers, students, and alumni. The research identifies three typologies of innovation: Modern-Progressive, Integration-Multiformat, and Traditional-Intensive. The study highlights the strategies pesantren employ to overcome challenges such as resource constraints, technological resistance, and socio-cultural barriers in order to maintain relevance amidst ever changing Muslim society in Indonesia. By integrating traditional Islamic education with modern pedagogical practices, these three pesantren enhance academic performance, foster character development, and equip students with 21st-century skills in their own way and method with different results and outcomes. This research contributes to the discourse on faith-based education by offering insights into how pesantren preserve their Islamic identity while innovating to meet contemporary societal needs.